Training of Making Creative Students’ Worksheet Based on Ethnomatematics by Using Edmodo App for Mathematics Teachers of MGMP of Junior High School in Payakumbuh City - Elita Zusti Jamaan; Ali Asmar; Arnellis Arnellis; Nonong Amalita; Media Rosha (Fakultas MIPA Universitas Negeri Padang, 2021)
The purpose of this study is to determine the creativity of teachers in designing ethnomathematical-based student worksheets through LMS - Edmodo at MGMP SMP Payakumbuh. Ethnomathematics based student activity sheet (LKS) is based on the local culture of Payakumbuh. This Ethnomathematics-based LKS is expected to be the initial foundation for teacher creativity to design and develop Ethnomathematics-based LKS in accordance with Payakumbuh City. The method used in the service is in the form of online and offline workshops. The target audience for this community service is the mathematics teacher in the Payakumbuh Mathematics Junior High School Subject Teacher Consultation. This training stage begins online with a zoom meeting, giving questionnaires, carrying out tests, then followed by making Ethnomathematics-based LKS with the Edmodo platform. The results of the implementation show that the creativity of teachers in designing Ethnomathematics-based worksheets using the Edmodo platform is good, with the percentage of achievement of 79% and the creative achievement of teachers in participating in this activity is 78%.